Development of optimal energy management for a residential fuel cell hybrid power system with heat recovery. (15th March 2021) - Ou, Kai; Yuan, Wei-Wei; Kim, Young-Bae
Abstract: Integration of heat recovery with proton exchange membrane fuel cell/battery-based hybrid power system, which is also known as a micro-combined heat and power (CHP) system, is a promising method to achieve higher output efficiency. The developed hybrid power system for a micro-CHP is applied to a residential house by supplying electric power and hot water simultaneously. When the fuel cell generates heat and electricity via the oxidation reaction of hydrogen with a working temperature of 70 °C, heat recovery is provided through internal cooling system. Energy management system (EMS) plays a crucial role in obtaining optimal fuel economy and promising the running stability. Optimal Pontryagin minimum principle is used as a real-time EMS by splitting the hybrid power (i.e., power between fuel cell and battery) to realize fuel minimization, battery protection, and hot water supply. Optimal energy management is achieved by considering the external load demand, state charge of a battery, and temperature of the thermal storage system. Simulation model is developed, and real experiments are performed to prove that the EMS can effectuate high efficiency and safe operation of a hybrid power system through optimal power split between fuel cell and battery powers. Highlights: Residential fuel cell – CHP system is optimized for increasing the performance. Optimal Pontryagin principle is used as a real-time EMS by splitting the hybrid power. Experimental results prove the effectiveness of the EMS in achieving high efficiency.